Integrated Agriculture Practices & Food Value Chain: A Futuristic Approach for Sustainable Growth & Income of Farmers and Farmer Producer Organizations (FPOs) - Kumar Thota, Bharath (Digital Repository of Theses, 2024)
This DBA thesis explores the potential of integrated agriculture practices and the food value chain as a futuristic option for ensuring sustainable growth and income for farmers and Farmer Producer Organizations (FPOs) especially related to Spices in Andhra Pradesh. With the growing challenges faced by the agricultural sector, including climate change, market volatility, and resource constraints, there is an urgent need to adopt innovative and holistic approaches. This thesis examines the concept of integrated agriculture, its various components, and how it can be seamlessly integrated into the food value chain of spices to benefit farmers and FPOs. The study combines theoretical analysis, empirical research, and case studies to provide insights into the transformative potential of this approach. In addition to examining integrated agriculture practices, the thesis investigates how these practices can be seamlessly integrated into the food value chain. The food value chain encompasses all the stages of production, processing, distribution, and consumption of food. By incorporating integrated agriculture into the food value chain, farmers and FPOs can achieve greater efficiency and value addition at each stage, leading to improved profitability and sustainability. The thesis combines theoretical analysis with empirical research and case studies to provide a comprehensive understanding of the transformative potential of integrated agriculture practices within the food value chain. Through these approaches, the study identifies successful models and strategies that can be replicated and adapted to different contexts. Moreover, the thesis evaluates the impact of integrated agriculture practices on the economic, social, and environmental aspects of farming. It assesses how these practices can contribute to food security, poverty reduction, and the empowerment of rural communities. The findings of the thesis offer valuable insights and recommendations for policymakers, agricultural practitioners, and FPOs seeking to adopt integrated agriculture practices and improve their participation in the food value chain. Ultimately, the thesis provides a roadmap for achieving sustainable growth and income for farmers and FPOs through innovative agricultural practices and value chain